REE-SR-BA MINERALS FROM THE KHIBINA CARBONATITES, KOLA PENINSULA, RUSSIA: THEIR MINERALOGY, PARAGENESIS AND EVOLUTION - Zaitsev A.N.; Wall F.; Le Bas M.J. (My University, 1998)
Carbonatites from the Khibina Alkaline Massif (360–380 Ma), Kola Peninsula, Russia, contain one of the most diverse assemblages of REE minerals described thus far from carbonatites and provide an excellent opportunity to track the evolution of late-stage carbonatites and their sub-solidus (secondary) changes. Twelve rare earth minerals have been analysed in detail and compared with literature analyses. These minerals include some common to carbonatites (e.g. Ca-rare-earth fluocarbonates and ancylite-(Ce)) plus burbankite and carbocernaite and some very rare Ba, REE fluocarbonates. Overall the REE patterns change from light rare earth-enriched in the earliest carbonatites to heavy rare earth-enriched in the late carbonate-zeolite veins, an evolution which is thought to reflect the increasing ‘carbohydrothermal’ nature of the rock-forming fluid. Many of the carbonatites have been subject to sub-solidus metasomatic processes whose products include hexagonal prismatic pseudomorphs of ancylite-(Ce) or synchysite-(Ce), strontianite and baryte after burbankite and carbocernaite. The metasomatic processes cause little change in the rare earth patterns and it is thought that they took place soon after emplacement.